Smart carbon fiber bicycle seat post with light and sensor integration - Kaufmann, J.; Rabe, H.; Siebert, N.; Wolf, P.; Cebulla, H.; Odenwald, S. (Procedia Engineering, 2016)
The development of high-performance sports equipment is nowadays focused on lightweight structure designs with integrated functions. Even in cycling an increasing number of manufacturers prefer to use fiber reinforced plastics (FRP) in their frames and further bicycle parts. During the manufacturing of these FRP-components it is possible to integrate flat and flexible electronics and sensors such as stitched strain gauges into semi-finished reinforcement textiles.